A Needs Analysis for Web-based English Medical Terminology Learning for Healthcare Practitioners: Insights from Quantitative and Qualitative Data - Runze, Jiang; Mohamad, Maslawati; Che Musa, Normazidah (Education in Medicine Journal, 2026)
English has become the dominant language in science and medicine, and proficiency in English medical terminology is essential for international communication, academic competence, and professional development. Despite ongoing national efforts to promote the internationalisation of medical education in China, healthcare practitioners continue to face significant barriers in learning English medical terminology, including linguistic complexity, limited resources, and time constraints. This study investigates the specific needs of Chinese healthcare practitioners to improve the efficiency of learning English medical terminology through a web-based learning resource (WBLR). Drawing on the needs analysis framework of Dudley-Evans and St John and adopting a mixed-methods design, the study analysed 417 valid questionnaires and conducted interviews with 22 stakeholders across 6 hospitals. The findings indicate that practitioners consider English medical terminology critical to academic and professional growth, yet face persistent challenges due to the scarcity of interactive, contextually relevant materials. Participants expressed strong preferences for bilingual, multimodal, and technology-enhanced learning, supported by adequate digital competence and reliable online access. Additionally, variations across educational levels highlight the need for instructional designs that accommodate diverse learner profiles. The study suggests that developing tiered, learner-centred, and context-responsive WBLR is essential to enhance the effectiveness and inclusivity of English medical learning.